Estimation, origine et composition des revenus des habitants dans les communes wallonnes - Xavier May (Belgeo)
Belgian statistics on income, generally used to study inhabitants’ income at commune level, depend on tax legislation and are far from the economic notion of income. We therefore propose an estimate of the net (after-tax) income available for the inhabitants of each of the 262 communes of Wallonia for the year 2001, including labour and property income as well as social transfers. Our database is the result of considerable effort to collect statistics and of estimates whenever data are lacking at commune level. In addition, we used the data from the 2001 census to assess which communes the inhabitants of a commune get their labour income from. On this basis two typologies have been developed: the first concerns the inhabitants’ income composition in the communes, the second the distance travelled by the inhabitants of a commune to earn this income.